(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Most of the disciplines taught in schools and universities and traditional scientific areas are hopelessly outdated. We live in a different vibrational and wave mode, in contrast to the mode of thinking of the twentieth century. Innovations in genetics, biochemistry, astrophysics and social sciences provide rich food for the development of the conceptual apparatus of philosophy. Therefore, the mode of thinking at the accelerating pace of the vibration of the planet cannot allow people to live according to the pattern of past years. In such conditions, new scientific and spiritual directions arise, which are engaged in the search for a correspondence to the mental activity of people. One of such search and reconnaissance disciplines of an integral nature is the scientific and practical discipline “Transhumanitarian Philosophy” (THP) proposed by us, which is built at the intersection of many sciences. A person with a new worldview is a person with a another (changed) reality. Therefore, the experienced situation dictates the presence of a nonlinear-wave view of time and space. Time is presented as energy, and space as an arrangement of temporary substances in a measuring order. The essential difference between THF and the traditional philosophical worldview is that THF seeks to communicate with the cosmic mind. Earth dimensions become cramped and anachronistic in many ways. It is no coincidence that humanity seeks to explore other planets and celestial bodies, starting the process of terraforming (Mars, the Moon, satellites of the gas giants Jupiter and Saturn, even hot Venus). Deciphering the circles in the wheat fields left by unknown travelers of Time will provide great educational material for curious minds. THF, as a trend of the times, is built on the basis of such scientific disciplines as philosophy, theoretical physics, natural sciences, sociology, geopolitics, law, futurology, history, economics, philology, cultural studies, as well as ecology, genetics, medicine and biochemistry. Spiritual disciplines such as theology (including Koranic and Biblical studies), Manas studies, yoga, ancient spiritual teachings (such as Vedanta, Hinduism, Buddhism, Taoism, Zoroastrianism) and Tengrianism (including shamanism) are interesting us for the future epistemological thinking. The practical side of the THF is to initiate public lectures, internal and international conferences, scientific and spiritual forums, exercises to develop a general scientific and practical concept of a new worldview. In this regard, it became necessary to note a number of promising scientific areas that require systematization and new methodological reflection.